A video based run-off-road training program with practice and evaluation in a simulator. (September 2015) - Freeman, Paul; Neyens, David M.; Wagner, John; Switzer, Fred; Alexander, Kim; Pidgeon, Philip
Highlights: The effect of a run-off-road training video was evaluated in a driving simulator. Positive effect found on driver steering response for all roadways tested. Improvements in vehicle stability and self-rated demand and performance for highway. Significant reduction in spin outs observed for trained participants. Abstract: A run-off-road (ROR) event occurs when one or more of a vehicle's wheels leaves the roadway and begins to travel on the surface or shoulder adjacent to the road. Despite various countermeasures, ROR crashes continue to yield a large number of fatalities and injuries. Infrastructure-based solutions do not directly address the critical factor of driver performance preceding and during an ROR event. In this study, a total of 75 individuals participated in a pre–post experiment to examine the effect of a training video on improving driver performance during a set of simulated ROR scenarios (e.g., on a high speed highway, a horizontal curve, and a residential rural road). In each scenario, the vehicle was unexpectedly forced into an ROR scenario for which the drivers were instructed to recover as safely as possible. The treatment group then watched a custom ROR training video while the control group viewed a placebo video. The participants then drove the same simulated ROR scenarios. The results suggest that the training video had a significant positive effect on drivers' steering response on all three roadway conditions as well as improvements in vehicle stability, subjectively rated demand on the driver, and self-evaluated performance in the highway scenario. Under the highway conditions, the treatment group reduced the frequency of spinouts from 70% in the pre-training events to 16% in the post-training events (χ 2 (1) = 23.32, p < 0.001) with no significant improvement found for the control group. In the horizontal curve, spinouts were reduced for the treatment group from 50% in the pre-training events to 30% in the post-training events (χ 2 (1) = 8.45, p = 0.004) with the control group also not showing any significant improvement. The results of this study suggest that even a short video about recovering from ROR events can significantly influence a driver's ability to recover. It is possible that additional training may have further benefits in recovering from ROR events.